Body dissatisfaction among male and female adolescents - Adeymend Reny Japil; Mazni Mustapha; Guan, Teik Eee (Unit Penyelidikan Psikologi dan Kesihatan Sosial UMS, 2017)
This study was conducted to investigate the relationship between body dissatisfaction and body mass index (BMI) among adolescents, and the differences of this subjective dissatisfaction in terms of BMI and gender. In total, 328 adolescents (147 males and 181 females) aged 16-year-old participated in the study. Eating Disorder Inventory – Body Dissatisfaction and Body Mass Index were used to collect quantitative data on respondents’ body dissatisfaction, and weight and height information for BMI. Pearson correlation showed that body dissatisfaction significantly correlated with BMI. One-Way ANOVA showed that subjective evaluation among underweight and normal weight adolescents significantly varied with dissatisfaction in the other two groups (overweight and obese adolescents). Body dissatisfaction among underweight adolescents was statistically significantly lower compared to overweight and obese adolescents. Body dissatisfaction among adolescents with normal weight is also statistically significantly lower compare to overweight and obese adolescents. There was no statistically significance difference on dissatisfaction between underweight and normal weight adolescents, and between overweight and obese adolescents. Interestingly, independent-samples t-test found that body dissatisfaction did not differ between male and female adolescents. This information is useful for the planning of health programs as well as intervention and prevention programs to combat adolescents’ body weight and body dissatisfaction problems.